PENGARUH SOSIAL BUDAYA DENGAN PEMBERIAN NUTRISI PADA IBU MENYUSUI DI POSYANDU MELATI CILACAP - Oktanasari, Wiji; Fitriyani, Tanti; Okta Ayuningtyas, Beby Yohana (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
There are still issues in society with the breastfeeding mother culture of dietary restriction. Despite its strong cultural beliefs, it is undeniable that this culture of food limitation may reduce the amount of nutrients that nursing moms need to consume. The purpose of the study is to use a type of case-control time survey approach to ascertain whether sociocultural factors have an impact on the nourishment provided to nursing mothers at Posyandu Melati Cilacap. Thirty-two breastfeeding women made up the study sample. A cross-sectional strategy is used in this quantitative study with a descriptive correlation research design. While Chi Square is used for data analysis and product moment correlation calculations are used for the validity test, Cronbach's Alpha is used for the reliability test. The findings of the chi square test, which yielded a p value (0.029) < 0.05, demonstrated that social culture had an impact on Posyandu Melati Cilacap's breastfeeding moms' access to nourishment. 2,046 breastfeeding mothers at Posyandu Melati have a strong correlation between social culture and nutrition. Based on research findings and recommendations, breastfeeding mothers are strongly encouraged to eat a healthy diet; there are no dietary restrictions because the mother's food intake has a significant impact on the production of breast milk.Keywords: Socio-Cultural, Nutrition, Breastfeeding Mothers